Cover Feature: Tubular Structures of Calcium Carbonate: Formation, Characterization, and Implications in Natural Mineral Environments (Chem. Eur. J. 65/2021). Issue 65 (10th November 2021) - Getenet, Melese; Rieder, Julian; Kellermeier, Matthias; Kunz, Werner; Manuel García‐Ruiz, Juan
Abstract : Calcium carbonate chemical gardens are tubular mineral structures precipitated upon the addition of sodium carbonate solution to calcium chloride pellets. The tubes are composed of texturally distinct bilayers of aggregates of rhombohedral and cone‐shaped calcite on their exterior and interior surfaces, respectively. These highly crystalline and dense bilayers prohibit the development of significant electrochemical potential differences across the tube walls. More information can be found in the Full Paper by M. Kellermeier, J. M. García‐Ruiz et al. (DOI: 10.1002/chem.202101417 ).